Pelaksanaan Hukum Adat Tentang Jual Beli Hak Atas Tanah Adat Kepada Orang Bukan Suku Tengger Berdasarkan Asas Keadilan - Putri, Jenuarani Artha Adinda (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the provisions for the sale and purchase rights to customary land of the Tengger tribe and implement common law regarding buying and selling to non-Tengger people based on justice. The research method used in this study was empirical juridical with a statutory approach. Data was collected by using interview and documentation techniques. Data sources consisted of primary data and secondary data. The study results showed that the Tenggerese community still maintained the provisions of customary law regarding the prohibition of buying and selling customary land to non-Tengger people. The sale and purchase of customary land of the Tengger tribe to non-Tengger people did not fulfil the principle of justice because it did not involve the customary head and the community's agreement.